Stryker's revenge a Ralph Compton novel - West, Joseph A.; Compton, Ralph (New York Signet, 2010)
An Army officer swears revenge on the gunrunner who scarred him.
At head of title: Ralph Compton.
96197
Keywords: Revenge; Western stories